Fabrication of nitrate ion sensor based on conductive polyaniline doped with nitrate using thick film technology - Charlotha Charlotha; Robeth Viktoria Manurung; Aminuddin Debataraja; Indra Dwisaputra; Subkhan Subkhan; Iqbal Syamsu (National Research and Innovation Agency, 2022)
Nitrate is one of the nutrients that can give an effect on the environment if it is applied in excess. It is also easily soluble in water and it has the potential to be a pollutant in groundwater by the over-process of fertilizer. Therefore, it needs a detected component to give the right measure for nitrate in the soil, called a nitrate ion sensor. It consists of three electrodes configuration, namely, working, counter, and reference electrodes with conductive polyaniline doped with Nitrate (NO₃‾) which is fabricated by thick film technology. In previous research, acidic media was used as a solvent for polyaniline, while this research used water (H2O) solvent. The result of characterization showed that particles were distributed evenly on the sample with the form of particles being small balls with a dimension of 0.18 µm and the percentage of atomic elements being: 91.96 % carbon, 3.14 % nitrogen, and 4.9 % oxygen. The performance of sensors was investigated using potentiostat with four concentrations of nitrate standard solution. The result showed good response with a voltage range in each concentration of nitrate standard solution being 0.5002 Volt (10 mg/l), 1.3552 Volt (20 mg/l), 1.1208 Volt (50 mg/l), and 0.8963 Volt (100 mg/l). It was found that nitrate sensors with nitrate-doped conductive polymer, polyaniline, as the sensitive membrane responded well to detecting nitrate elements in precision farming and the sensitivity showed that for every 1 mg/l concentration in nitrate standard solution, the voltage increases by 0.0007.